Words, clauses, sentences, and T-units in learner language: Precise and objective units of measure?. (7th August 2020) - Mylläri, Taina
In research on learner language complexity, accuracy and fluency (CAF), syntactic complexity is often studied with quantitative measures based on words, clauses, sentences, and T-units. The findings have been mixed, but segmenting learner language into these units of measure has seldom been problematised, even if the need for accurate coding is well known. The present study explores words, clauses, sentences, and T-units as production units in written learner language using a corpus of 352 L2 Finnish texts (28, 813 words). The results illustrate how written learner language can be hard to fit into the production unit categories, which are essential for the most frequently used quantitative measures of syntactic complexity. On the one hand, the results support calls to include explicit definitions of the units of measure when reporting findings obtained with these quantitative measures. On the other hand, they align with calls to introduce new measures to better gauge the changes in learner language syntax as it develops with increasing language proficiency.